ANALISIS KEMAMPUAN LITERASI MATEMATIS MAHASISWA DALAM PEMECAHAN MASALAH EKSPRESI ALJABAR DI UIN SYAHADA PADANGSIDIMPUAN - Rama Nida Siregar (Afore : Jurnal Pendidikan Matematika, 2026)
Mathematical literacy is an essential competency that students must possess to understand, model, and solve mathematical problems, particularly in algebraic expressions, which remain challenging for many students. This study aims to analyze students’ mathematical literacy skills in solving algebraic expression problems. The research employed a qualitative approach using a descriptive method conducted among students at UIN Syahada Padangsidimpuan. The participants consisted of 20 students selected through purposive sampling and categorized into high, moderate, and low ability levels. Data were collected through essay-based tests and in-depth interviews, while data analysis followed an interactive model involving data reduction, data display, and conclusion drawing. The findings revealed that students’ mathematical literacy skills were distributed into three categories: high (35%), moderate (40%), and low (25%). Students in the high category demonstrated strong abilities in understanding, modeling, and solving problems systematically, whereas those in the moderate and low categories experienced difficulties in mathematization, reasoning, and problem-solving strategies. The findings imply the need for instructional strategies that emphasize conceptual understanding, mathematical reasoning, and systematic problem-solving practices to enhance students’ mathematical literacy skills.